INTEGRASI EDUKASI PERTANIAN DALAM PENGEMBANGAN AGROWISATA SEKOLAH - Sari, Diyan Retno (Tahta Media Group, 2024)
This study aims to analyze institutional strategies, structural challenges, and development opportunities of school-based agrotourism through agricultural education integration at SMP Muhammadiyah Plus Doro. The research employed a qualitative case study approach. Data were collected through in-depth interviews, participant observation, and document analysis, and examined using an interactive analysis model. The findings indicate that the development of school agrotourism is supported by project-based curriculum integration, transformational leadership, and partnerships with local agrarian communities. Key challenges include limited human resource capacity, inadequate facilities, and curriculum scheduling constraints. However, the agrarian environment and the growing interest in educational tourism provide significant opportunities for program sustainability. The integration of agricultural education enhances students’ environmental literacy, practical skills, and entrepreneurial awareness as part of sustainable education practices.